Caracterização molecular e isolamentode clostrídios psicrofílicos e psicrotróficos associados à deterioração de carnes refrigeradas embaladas a vácuo - BUENO, Cláudia Peixoto (2009)
The deterioration of vacuum packed refrigerated meat accompanied by large gas production - a phenomenon called blown pack - is considered a major cause of economic losses of the meat industry in several regions of Brazil and the world. Several psychrophilic and psychrotrophic microorganisms may be involved, especially species of Clostridium. The objective of the present study was to perform the molecular characterization, through the use of the PCR technique, and the molecular isolation by conventional bacteriology, of the main microorganisms that cause blown pack in refrigerated meat from Brazil, New Zealand and the United Kingdom. Thus, typing techniques were used to differentiate the species and subspecies involved in this type of deterioration. Tirty-six samples of Brazilian blown pack meat, 6 samples from the UK and 12 experimental blown pack samples of venison from the North Island of New Zealand were analyzed. Three pairs of primers, the RFP / RRP, the 16SEF/16SER and the pair EISRF / EISRR were used for C. estertheticum estertheticum and Clostridium estertheticum like, and one for C. gasigenes (16DBF/16DBR). The samples with the PCR results were sent to a microbiology laboratory for conventional isolation of Clostridium estertheticum. It was concluded that Clostridium estertheticum estertheticum is responsible for the deterioration of meat and hence the blown pack in the UK. Samples of blown pack Brazilian meat have Clostridium estertheticum like as primary causal agent. The typing was carried out in isolates and strains - donated by Mirinz Center / Ruakura Agresearch / Hamilton / New Zealand - together with two isolates from Brazil, involved in this type of deterioration. The selected techniques AFLP and RFLP - PCR were able to distinguish species and subspecies of psychrophilic and psychrotrophic clostridia. However, the AFLP showed the highest discriminatory power, being able to distinguish 100% of the species - C. estertheticum, C. frigoris, C. bowmani, C. lacusfryxellense and C. psychrophylum - and also the subspecies C. estertheticum estertheticum, C. estertheticum laramiense, C. estertheticum like k21 and k24. Through the technique of RFLP, it was possible to differentiate the species of clostridia psychrotrophic, psichrophilic and also the subspecies C. estertheticum estertheticum and Clostridium estertheticum like, along with the use of four restriction endonucleases - AluI, CfoI, TaqI and HaeIII. The HaeIII provided greater variety of fragments and the ability to differentiate the species of clostridia psychrophilic and psychrotrophic, whereas TaqI was the only enzyme capable of differentiating the subspecies of C. estertheticum estertheticum and C. estertheticum laramiense of C. estertheticum like. The Brazilian samples isolated fit into the group of Clostridium estertheticum like, although there is no confirmation of the absence of Clostridium estertheticum estertheticum in the country.